A new route to the fabrication of Si3N4/SiC nanocomposite - Kim, CS; Oh, YS; Cho, WS; Lim, DS; Cheong, DS (TRANS TECH PUBLICATIONS LTD, 1999)
We attempted in-situ fabrication of Si3N4/SiC nanocomposite using commercial polymer such as phenolic resin. The essential point is that the bonds between the carbon and the other elements in polymer can be removed by simple thermal treatment, thereby producing free carbon. In mixture containing both the Si3N4 powder, which contained some amount of SiO2 impurity, and polymer, SiC nanoparticles were considered to be formed by direct reaction between carbon and Si species (Si3N4 and/or SiO2). The SiC particles were well dispersed in the matrix. We examined residual free carbon in the final nanocomposite using Raman spectroscopy, concluding that the carbon did not exist.
Keywords: SILICON-CARBIDE; MECHANICAL-PROPERTIES; CARBON-FILMS; PRECURSORS; CERAMICS; POLYMER; MICROSTRUCTURE; PYROLYSIS; COMPOSITE